Periprostatic fat tissue transcriptome reveals a signature diagnostic for high-risk prostate cancer. Issue 5 (May 2018) - Mangiola, Stefano; Stuchbery, Ryan; Macintyre, Geoff; Clarkson, Michael J; Peters, Justin S; Costello, Anthony J; Hovens, Christopher M; Corcoran, Niall M
Abstract : Evidence suggests that altered adipose tissue homeostasis may be an important contributor to the development and/or progression of prostate cancer. In this study, we investigated the adipose transcriptional profiles of low- and high-risk disease to determine both prognostic potential and possible biological drivers of aggressive disease. RNA was extracted from periprostatic adipose tissue from patients categorised as having prostate cancer with either a low or high risk of progression based on tumour characteristics at prostatectomy and profiled by RNA sequencing. The expression of selected genes was then quantified by qRT-PCR in a cross-validation cohort. In the first phase, a total of 677 differentially transcribed genes were identified, from which a subset of 14 genes was shortlisted. In the second phase, a 3 gene ( IGHA1, OLFM4, RERGL ) signature was refined and evaluated using recursive feature selection and cross-validation, obtaining a promising discriminatory utility (area under curve 0.72) at predicting the presence of high-risk disease. Genes implicated in immune and/or inflammatory responses predominated. Periprostatic adipose tissue from patients with high-risk prostate cancer has a distinct transcriptional signature that may be useful for detecting its occult presence. Differential expression appears to be driven by a local immune/inflammatory reaction to more advanced tumours, than any specific adipose tissue-specific tumour-promoting mechanism. This signature is transferable into a clinically usable PCR-based assay, which in a cross-validation cohort shows diagnostic potential.